Systematic review and meta-analysis investigating osmolyte concentrations of marine osmoconformers under low salinity stress - Imke Anna Podbielski; Lara Schmittmann; Trystan Sanders; Frank Melzner (PANGAEA, 2023)
Climate change is predicted to alter salinity in many coastal regions. This exerts significant physiological stress on coastal invertebrates whose body fluid osmolality follows that of seawater ( extquotesingleosmoconformers extquotesingle). Osmolytes are the cellular actors in osmoconformers that regulate acclimation to salinity changes. Inspite of their cellular importance in salinity tolerance, cellular volume regulation and its osmotic components, are not sufficiently understood. Which compounds are commonly used as osmolytes? Are inorganic and organic osmolytes used in long-term salinity acclimation? Are there taxonomic- or tissue specific differences? By conducting an extensive literature search, this study aimed to answer these questions. By using a meta-analysis approach over an ordinary literature review we were able to statistically evaluate the individual effect sizes by computing a summary effect for multiple studies to estimate the mean of the distribution of the true effect sizes. Meta-analysis is useful to reveal research gaps, common actors across taxa, or overall effects of biotic factors. We thus conducted a systematic review and meta-analysis of osmolyte data (both organic and inorganic) utilized by osmoconforming marine invertebrates during a >14-day acclimation to reduced salinity. This study offers a valuable overview of the various listed organic compounds across species and whether and in which organisms they are used as osmolytes under low salinity stress. This study thereby creates a valuable baseline for future research. 2389 studies were screened according to standard systematic review procedures (title scan, abstract scan and full-exam) resulting a total of 56 studies that fulfilled the search criteria. The data includes the list of all papers that underwent a full-exam in the systematic review process and passed the search criteria and study details of the studies used for meta-analysis. For all included studies the input data necessary to conduct a meta-analysis with a hedge extquotesingles g effect size is given. Namely, mean osmolyte concentrations, variance measure and replicate numbers are given for the high and low salinity treatment. The data for any benthic osmoconforming species and any osmolyte type is included. The data table is sorted by study but gives additional information on taxonomy, experimental details, study design, osmolyte type, tissue type, etc. Additionally, data is available for a number of studies that reported an extensive osmolyte budget (i.e. multiple compounds). Here, for each study and study organism osmolytes (that were present in more than one study) are listed as percent of the total organic osmolyte pool. This dataset is the first systematically compiled list of studies investigating osmolyte concentrations in osmoconformers after long-term (>14 days) acclimation to low salinity. Data can be used to compare own osmolyte data (species/osmolyte compound) with a comprehensive list of osmolyte literature data. Additionally, this data can be used to address other hypotheses via meta-analysis. As this was a systematic review, no biological samples were collected in this study. Information of the origin of the data from each of the included studies can be found in the list of all included studies.